2020
DOI: 10.1101/2020.08.28.271957
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of 14 Known Drugs as Inhibitors of the Main Protease of SARS-CoV-2

Abstract: A consensus virtual screening protocol has been applied to ca. 2000 approved drugs to seek inhibitors of the main protease (Mpro) of SARS-CoV-2, the virus responsible for COVID-19. 42 drugs emerged as top candidates, and after visual analyses of the predicted structures of their complexes with Mpro, 17 were chosen for evaluation in a kinetic assay for Mpro inhibition. Remarkably 14 of the compounds at 100-μM concentration were found to reduce the enzymatic activity and 5 provided IC50 values below 40 μM: manid… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
61
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(65 citation statements)
references
References 49 publications
0
61
0
4
Order By: Relevance
“…2, 3-Panel C). Intriguingly, this in-silico hypothesis has recently found two independent experimental validations, which have highlighted a mild inhibitory activity of Nelfinavir against the SARS-CoV-2 M pro (estimated between 250 and 600 μM) 25,26 . www.nature.com/scientificreports/ lar dynamics (MD) simulations were performed with an ACEMD3 engine on an Nvidia GPU cluster composed of 20 NVIDIA drivers, whose models go from GTX 1080 to Titan V 28 .…”
Section: Discussionmentioning
confidence: 87%
“…2, 3-Panel C). Intriguingly, this in-silico hypothesis has recently found two independent experimental validations, which have highlighted a mild inhibitory activity of Nelfinavir against the SARS-CoV-2 M pro (estimated between 250 and 600 μM) 25,26 . www.nature.com/scientificreports/ lar dynamics (MD) simulations were performed with an ACEMD3 engine on an Nvidia GPU cluster composed of 20 NVIDIA drivers, whose models go from GTX 1080 to Titan V 28 .…”
Section: Discussionmentioning
confidence: 87%
“…4H) . Glu166 of this segment is actually an important residue that plays a role in stabilizing the substrate binding site S1 by interacting with Ser1 of the alternate protomer along with Phe140 (Ghahremanpour et al, 2020; Jin et al, 2020) and we observed that along PC1, for protomer A of 7CWB and protomer B of 7CWC, the motions of these residues are correlated. This could have implications about information transfer from one protomer to the other though other Mpro structures of SARS-CoV-2 needs to be studied in atomistic details.…”
Section: Resultsmentioning
confidence: 66%
“…This new structure was derived from crystals obtained with Mpro pre-incubated with inhibitors masitinib, manidipine or bedaquiline, however in no cases electron densities indicating the presence of the inhibitors were detected. This is explainable by the reported medium/low IC50 (in the range 2.5-19 µM) (Drayman et al, 2020;Ghahremanpour et al, 2020) and by the very low aqueous solubility of the molecules (when inhibitors in 100% DMSO were added to the protein solution visible white precipitates appeared). Notably, some structures from crystals coming from cocrystallization experiments with the same inhibitors pre-incubated with Mpro show the oxyanion canonical conformation, indicating that these molecules are not strict determinants for the new conformation.…”
Section: Resultsmentioning
confidence: 91%
“…In a campaign to get structural insights on SARS-CoV-2 Mpro we analyzed 27 different datasets to determine the crystal structure of Mpro in complex with inhibitors, namely masitinib, manidipine and bedaquiline (Ghahremanpour et al, 2020). Among these, as "positive" controls (i.e.…”
Section: Resultsmentioning
confidence: 99%